Pattern and trends of the Iban, Chinese and Malay populations of Sarawak, 1947-2010 - Lam Chee, Kheung (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Sarawak is the largest State among the thirteen States in the Federation of Malaysia. It straddles across the north-west of the island of Borneo, having an area of approximately 124,449.5 square kilometers, comprising eleven administrative divisions, and these divisions are further sub-divided into 31 administrative districts. Sarawak is a multi-ethnic society in which the six major communities, according to priority order in number, are Iban, Chinese, Malays, Bidayuh, Orang Ulu and Melanau. These ethnic communities have had distinctive cultural, social and economic conditions which yield different demographic behaviors, levels and changes in birth and death rates. Based on the above perceptions, this book applies the census data, births and deaths registration and vital statistics from the government sources to measure the demographic differentials, dynamics of growth and change of population among the three major ethnic communities, namely the Iban, Chinese and Malay, and identify the economic, social and cultural factors influencing these pattern and trends of population for the last 60 years, from 1947 to 2010.